Sintesis Enkapsulasi Ekstrak Kunyit (Cursuma longa. L) Berbasis Karboksimetil Kitosan sebagai Penghantaran Obat: indonesia - Ainaia Deaqiila Wahyudi; Sari Edi Cahyaningrum (Unesa Journal of Chemistry, 2024)
Curcumin is the main bioactive compound in turmeric (Curcuma longa L.) with high antioxidant activity, yet its application is limited due to poor solubility and low stability under physiological conditions. This study aimed to synthesize and characterize curcumin-encapsulated nanoparticles based on carboxymethyl chitosan (Cur-NPs) as a more stable drug delivery system. The synthesis was performed using the sonication method, while characterization included particle size and polydispersity index (PDI) analysis via PSA dan pH stability testing. The results showed that Cur-NPs had a particle size of 281.3 nm and a PDI of 0.3897, indicating a uniform particle distribution. Cur-NPs exhibited greater stability than turmeric extract across various pH conditions (2-10). These findings demonstrate that curcumin encapsulation using CMC can enhance the stability and release efficiency of curcumin in biological systems.